Step
*
of Lemma
bag-map-equal
∀[T,A:Type].
  ∀f,g:T ⟶ A. ∀P:T ⟶ 𝔹.
    ((∀x:T. ((¬↑(P x)) 
⇒ ((f x) = (g x) ∈ A)))
    
⇒ (∀as:bag(T). ((↑null([x∈as|P x])) 
⇒ (bag-map(f;as) = bag-map(g;as) ∈ bag(A)))))
BY
{ (Fold `bag-null` 0 THEN Auto THEN Auto) }
1
1. T : Type
2. A : Type
3. f : T ⟶ A
4. g : T ⟶ A
5. P : T ⟶ 𝔹
6. ∀x:T. ((¬↑(P x)) 
⇒ ((f x) = (g x) ∈ A))
7. as : bag(T)
8. ↑bag-null([x∈as|P x])
⊢ bag-map(f;as) = bag-map(g;as) ∈ bag(A)
Latex:
Latex:
\mforall{}[T,A:Type].
    \mforall{}f,g:T  {}\mrightarrow{}  A.  \mforall{}P:T  {}\mrightarrow{}  \mBbbB{}.
        ((\mforall{}x:T.  ((\mneg{}\muparrow{}(P  x))  {}\mRightarrow{}  ((f  x)  =  (g  x))))
        {}\mRightarrow{}  (\mforall{}as:bag(T).  ((\muparrow{}null([x\mmember{}as|P  x]))  {}\mRightarrow{}  (bag-map(f;as)  =  bag-map(g;as)))))
By
Latex:
(Fold  `bag-null`  0  THEN  Auto  THEN  Auto)
Home
Index